The Taxonomy of multiseed Junipers (Juniperus sect.Sabina) in southwest Asia and East Africa (Taxonomic notes on Cupressaceae I) - Farjon, A. (Edinburgh Journal of Botany, 2010)
An extensive study of herbarium specimens and literature of arborescent multiseed Junipers (Juniperus L. sect. Sabina (Mill.) Spach) from SW Asia and E Africa, in preparation of a monographic volume “Drawings and Descriptions of Cupressaceae”, has led to a substantially revised concept of taxa and their distribution. A total of 18 species and 7 varieties were previously recognized in this group; most turned out to be synonyms. J. foetidissima var. pindicola Formanek, J. macropoda Boiss., J. procera Hochst. ex Endl., J. sabinoides Griseb., J. schugnanica Komarov and J. semiglobosa Regel were lectotypified; J. polycarpos K. Koch has been neotypified. The following taxa answering to the above circumscription are here recognized for the area: J. excelsa M.-Bieb., J. excelsa subsp. polycarpos (K. Koch) Takhtajan, J. foetidissima Willd., J. semiglobosa Regel, J. phoenicea L. and J. procera Hochst. ex Endl.